Effects of vegetation on open channel flow - Zhang, Qian (2009)
The report describes the effects of vegetation on open channel flow. Due to the presence of vegetation, the flow is affected by the drag force. Therefore, the flow property becomes much different from the non-vegetated flow. It has been an interest of research for a long time, to which many scholars have contributed their initiatives in order to improve the description of those effects.